Chinese migrants in Africa : study of the relations and interactions with Nigeria - (:unkn) unknown (My University, 2015)
The rising influence of China in Africa is often considered as the mere expression of the will the Chinese state. The role of migrants and Diasporas contributes decisively to the dynamism of these interactions. This is notably the case of the Chinese in Nigeria. Between China and Nigeria, inter-state relations carry little significance, unlike the interactions associated with the presence of Chinese migrants and entrepreneurs. The Chinese communities are solidly anchored in the Nigerian economic issue, and they create a momentum that combines business with politics. The thesis highlights anddiscusses, through observer-participant observations and interviews (both formally and informally conducted) the impulse given by an 'economic Diaspora' that remains largely autonomous vis a visofficial relations. We analyze daily strategies and contrast these with official relations. In doing so, the thesis decrypts the daily strategies and the importance of ordinary individuals and their networks in the development of a diversity of networks that contribute, in their own way, to deepen Sino-Nigerian interactions.
Keywords: African Research